Pengembangan Area Etika, Moral, Mediko-Legal dan Profesionalisme Serta Keselamatan Pasien dalam Kurikulum Berbasis Kompetensi - Yani Istadi (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2013)
Background: The existence of the application of competency-based curriculum (CBC) with the strategy of problem based learning (PBL) has influenced the learning process of ethics and professionalism. It poses a challenge for every medical school to develop the new curriculum. There has been a controversy on the model of the curriculum development. This article describes several educational studies on ethics and professionalism and proposes one curriculum model.Method: Relevant literatures are selected as basis of ethics and professionalism development in certain curriculum.Results: The method used in the study of ethics is directed in accordance with the level of education and the complexity of the expertise field. Determination of the material depends on the competence and the expected outcomes. Challenges in the assessment and ethics and professionalism must be faced.Conclusion: The development of a curriculum that will better ensure the achievement of competence 7th SKDI area. Therefore, the curriculum makers must continue to innovate.